Personal Branding Influencer di Media Sosial Denngan Kepustusan Pembelian Produk - Lilik Dwi Hariyanto; Wulandari, Intan; Wigati, Denok; Chintya Dewi, Windy (Universitas Darul Ulum, 2025)
This study aims to examine the relationship between personal branding influencers on social media and product purchasing decisions among teenagers. The subjects of this study were 75 students from MAN 4 Jombang. The sampling method used in this study was Purposive Random Sampling, with sample criteria being students aged 17 to 19 years. Data collection used in this study was a questionnaire and a Google form consisting of a 35-item personal branding influencer scale and a 45-item purchasing decision scale. Based on the Pearson Product-Moment statistical analysis, it is known that the correlation value rxy = 0.473, p = 0.000, where p <0.05 means that the higher the personal branding influencer on social media, the higher the consumer's purchasing decision on the product. Therefore, it can be concluded that the hypothesis in this study is accepted, namely that there is a relationship between personal branding influencers on social media and product purchasing decisions among teenagers.